Acanthamoeba Keratitis – A Case Report - Joshi, Leesha Shrestha; Gurung, Reeta (Nepalese Journal of Ophthalmology, 2021)
Introduction: Acanthamoeba keratitis is a serious infection of the cornea which causes severe inflammation of the eye and loss of vision. Case description: A 45 years female came with a history of trauma of right eye with vegetative matter with severe pain and redness. Patient was treated with antibacterial, antifungal eye drops but the condition deteriorated. Diagnosis was based on presence of motile trophozoites and cyst in the culture of non nutrient agar with a lawn of E coli of the corneal ulcer scraping. Therapeutic penetrating keratoplasty was performed as the patient’s condition deteriorated. Conclusion: Acanthamoeba keratitis is a rare parasitic vision threatening infection with poor prognosis in comparison to other infectious keratitis. Therefore prevention is very important.